2020
DOI: 10.1038/s41598-020-71143-2
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of the ddx5 gene in zebrafish sex differentiation and oocyte maturation

Abstract: DEAD-box helicase 5 (Ddx5) functions as an ATP-dependent RNA helicase and as a transcriptional coactivator for several transcription factors; however, the developmental function of the ddx5 gene in vertebrates is not fully understood. We found that the zebrafish ddx5 gene was expressed in developing gonads. Using the genome editing technology transcription activator-like effector nuclease, we established a ddx5-disrupted zebrafish and examined the morphological phenotypes of the mutant. We found that the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…DDX5 is a member of the DEAD-box RNA helicase family, which controls ribonucleoprotein formation [ 42 ]. DDX5 normally functions by performing as a transcriptional co-activator of several transcription factors and has been shown to motivate tumorigenesis and cancer progression [ 43 , 44 ]. Furthermore, under hypoxic conditions, DDX5 is elevated by miR-462 and restrains cell advancement by blocking cell cycle progression of DNA replication [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…DDX5 is a member of the DEAD-box RNA helicase family, which controls ribonucleoprotein formation [ 42 ]. DDX5 normally functions by performing as a transcriptional co-activator of several transcription factors and has been shown to motivate tumorigenesis and cancer progression [ 43 , 44 ]. Furthermore, under hypoxic conditions, DDX5 is elevated by miR-462 and restrains cell advancement by blocking cell cycle progression of DNA replication [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of Bxy-laf-1 significantly reduced the female to male sex ratios of B. xylophilus . Related genes of the DEAD-box family are involved in sex differentiation in C. elegans ( Hubert and Anderson, 2009 ), zebrafish ( Sone et al, 2020 ) and channel catfish ( Tian et al, 2017 ). Our results found that after Bxy-laf-1 dsRNA interfered with B. xylophilus , the ratio of female to male in F0 and F1 generations was significantly reduced, indicating that Bxy-laf-1 is involved in the development of sexual differentiation in B. xylophilus .…”
Section: Discussionmentioning
confidence: 99%
“…Gata6 is expressed in the ovary during embryonic development and is crucial for follicle assembly, granulosa cell differentiation, postnatal follicle growth, and the luteinization [ 68 ], while Ddx5 is expressed by spermatogonia in mice and acts as a transcriptional co-activator in the germline maintenance [ 55 ]. In zebrafish, ddx5 was expressed in developing gonads, and it is dispensable for testes development but essential for female sex differentiation and oocyte maturation [ 69 ]. In this study, ddx5 was differentially expressed at the bud stage with much higher expression in XX females, which suggests that this gene is more important to the development of female yellow catfish.…”
Section: Discussionmentioning
confidence: 99%